Social Security for Female Headed Households to Responses Covid-19 in Indonesia and Philippines - Binaridha Kusuma NIngtyas; Itok Wicaksono (Universitas Brawijaya, 2023)
This research examines a comparison of Philippines and Indonesian approaches to integrating a gender perspective in social protection programs. In the context of the COVID-19 pandemic, gender-responsive social protection has become even more important to address gender inequality which has been exacerbated by this crisis. The results of the study show that the Philippines has taken a more advanced step in paying attention to a gender perspective in social protection programs. They have launched clear policies and initiatives to ensure that women receive appropriate protection and appropriate services. On the other hand, Indonesia is still facing challenges in comprehensively integrating a gender perspective into social protection programs. This study provides insights and recommendations for both countries in implementing social protection programs that are sustainable and inclusive, with a focus on empowering women and overcoming gender inequality during the pandemic and in the future.